2013
DOI: 10.1353/jsm.2013.0002
|View full text |Cite
|
Sign up to set email alerts
|

Image Repair Through TV : The Strategies of McGwire, Rodriguez and Bonds

Abstract: This study critically analyzes Mark McGwire, Alex Rodriguez and Barry Bonds' defense of their steroid use and attempts at image repair during respective television interviews, applying the theory of image restoration discourse (Benoit, 1994). Rodriguez and McGwire used the same basic strategies of bolstering, mortification and blame shifting, while Bonds used denial and attacking his accuser. McGwire and Rodriguez used an "apologize-and-move-on" approach, while Bonds denied and continues to deny steroid use. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The “‘market value’ of an athlete’s [or organization’s] image hinges on…public reputation,” Brazeal (2008) contends, serving as the financial crux on which sports enterprises rest (p. 146). Because of this delicate relationship, athletes and organizations work overtime to avoid negative associations (Nelson, 1984; Coombs & Holladay, 2004; Walsh & McAllister-Spooner, 2011; Utsler & Epp, 2013; Koerber & Zabara, 2017; Jerome & Russell, 2018; Brown et al, 2020; Hanna & Morton, 2020). Every effort is made not to “admit wrongdoing” because it can “damage a player’s” or organization’s “long-term negotiating position” (Brazeal, 2008, p. 149), meaning athletes and organizations will go to great lengths to protect themselves (Coombs & Osborne, 2012; L’Etang, 2006; L’Etang & Hopwood, 2008).…”
Section: Sports Kategoria and Ownershipmentioning
confidence: 99%
“…The “‘market value’ of an athlete’s [or organization’s] image hinges on…public reputation,” Brazeal (2008) contends, serving as the financial crux on which sports enterprises rest (p. 146). Because of this delicate relationship, athletes and organizations work overtime to avoid negative associations (Nelson, 1984; Coombs & Holladay, 2004; Walsh & McAllister-Spooner, 2011; Utsler & Epp, 2013; Koerber & Zabara, 2017; Jerome & Russell, 2018; Brown et al, 2020; Hanna & Morton, 2020). Every effort is made not to “admit wrongdoing” because it can “damage a player’s” or organization’s “long-term negotiating position” (Brazeal, 2008, p. 149), meaning athletes and organizations will go to great lengths to protect themselves (Coombs & Osborne, 2012; L’Etang, 2006; L’Etang & Hopwood, 2008).…”
Section: Sports Kategoria and Ownershipmentioning
confidence: 99%
“…Research evidence would support such a stance. A study of the public relations strategies adopted by three leading US baseball players accused of doping (Utsler & Epp, 2013) found that an "apologise and move on" strategy was more effectiveeliciting support from teammates and fans -than a strategy of denial -negative responses from teammates and fans -as it provokes the media to seek out contradictions.…”
Section: Confession or Acquiescencementioning
confidence: 99%